Serum Tryptophan Metabolite Levels During Sleep in Patients With and Without Irritable Bowel Syndrome (IBS). (March 2016) - Heitkemper, Margaret M.; Han, Claire Jungyoun; Jarrett, Monica E.; Gu, Haiwei; Djukovic, Danijel; Shulman, Robert J.; Raftery, Daniel; Henderson, Wendy A.; Cain, Kevin C.
Poor sleep and stress are more frequently reported by women with irritable bowel syndrome (IBS) than by healthy control (HC) women. The pathophysiology linking poor sleep and stress to gastrointestinal symptoms remains poorly understood. We used a metabolomic approach to determine whether tryptophan (TRP) metabolites differ between women with and without IBS and whether the levels are associated with sleep indices and serum cortisol levels. This study sample included 38 women with IBS and 21 HCs. The women were studied in a sleep laboratory for three consecutive nights. On the third night of the study, a social stressor was introduced, then blood samples were drawn every 20 min and sleep indices were measured. Metabolites were determined by targeted liquid chromatography tandem mass spectrometry in a sample collected 1 hr after the onset of sleep. The ratios of each metabolite to TRP were used for analyses. Correlations were controlled for age and oral contraceptive use. Melatonin/TRP levels were lower ( p = .005) in the IBS-diarrhea group versus the IBS-constipation and HC groups, and kynurenine/TRP ratios tended to be lower ( p = .067) in the total IBS and IBS-diarrhea groups compared to HCs. Associations within the HC group included melatonin/TRP with polysomnography-sleep efficiency ( r = .61, p = .006) and weaker positive correlations with the other ratios for either sleep efficiency or percentage time in rapid eye movement sleep ( r > .40, p = .025–.091). This study suggests that reductions in early nighttime melatonin/TRP levels may be related to altered sleep quality in IBS, particularly those with diarrhea.